A novel lectin from mushroom Phellodon melaleucus displays hemagglutination activity, and antitumor activity in a B16 melanoma mouse model - Yuanhui Li; Peng Wang; Zejun Zhang; Qinghong Liu (Food Science and Human Wellness)
A novel lectin (termed PML) was purified from fruiting bodies of the edible mushroom Phellodon melaleucus (division Basidiomycota) by ion exchange, hydrophobic interaction, and gel filtration chromatographies, with overall titer recovery ~60 % and 20-fold purification. PML displayed hemagglutination activity 13319 units/mg toward rabbit erythrocytes. SDS-PAGE and gel filtration analyses revealed that PML is a homodimeric lectin with a molecular weight of 28.8 kDa. PML hemagglutination activity was not inhibited by various simple sugars or their derivatives, but was enhanced by cations Ca2+, Mg2+, Zn2+, and Cu2+. The activity was stable in pH range 6–9 and in the temperature range 20–60 °C. Circular dichroism (CD) spectroscopic analysis showed that PML was composed primarily of β-sheets with low α-helix content. In a B16 melanoma mouse model, PML treatment significantly inhibited tumor growth, and increased cytokine IL-10 content. Our findings suggest that PML is a potential anticancer therapeutic agent.